2020
DOI: 10.33490/jkm.v6i2.292
|View full text |Cite
|
Sign up to set email alerts
|

Pemberian Ekstrak Daun Kelor terhadap Peningkatan Kadar Hemoglobin pada Remaja Putri Putus Sekolah Usia 12 – 18 Tahun

Abstract: Teenage girls are prospective mothers who will give birth to the nation's next generation. Anemia among teenage girls causes the risk of giving birth to low birth weight babies (LBW) so that it has an impact on the optimal quality of life (bleeding, infection, abortion, low birth weight, premature, and defects congenital). Moringa leaves contain high amounts of vitamin A, vitamin C, vitamin B, calcium, potassium, iron, and protein which are easily digested and assimilated by the human body. Moringa oleifera ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Daun kelor adalah daun dari pohon kelor yang mengandung berbagai zat gizi makro dan mikro serta bahan-bahan aktif yang bersifat sebagai antioksidan. Daun kelor juga mengandung nutrisi penting seperti zat besi (fe) 28,2 mg, kalsium (ca) 2003,0 mg dan vitamin A 16,3 mg kaya β-karoten,protein, vitamin A, C, D, E, K, dan B (tiamin, riboflavin, niasin, asam pantotenat, biotin, vitamin B6, vitamin B12, dan folat) (Anwar, Hadju, Samrichar, Unde, Usman, & Mastuti, 2020). Berbagai jenis senyawa antioksidan seperti asam askorbat, flavonoid, fenolat dan karotenoid.…”
Section: Pembahasanunclassified
“…Daun kelor adalah daun dari pohon kelor yang mengandung berbagai zat gizi makro dan mikro serta bahan-bahan aktif yang bersifat sebagai antioksidan. Daun kelor juga mengandung nutrisi penting seperti zat besi (fe) 28,2 mg, kalsium (ca) 2003,0 mg dan vitamin A 16,3 mg kaya β-karoten,protein, vitamin A, C, D, E, K, dan B (tiamin, riboflavin, niasin, asam pantotenat, biotin, vitamin B6, vitamin B12, dan folat) (Anwar, Hadju, Samrichar, Unde, Usman, & Mastuti, 2020). Berbagai jenis senyawa antioksidan seperti asam askorbat, flavonoid, fenolat dan karotenoid.…”
Section: Pembahasanunclassified
“…Daun kelor merupakan salah satu bahan pangan yang memiliki potensi baik untuk melengkapi kandungan zat gizi dalam tubuh, meningkatkan energi dan ketahanan tubuh serta untuk mengatasi keluhan akibat kekurangan mineral seperti kekurangan zat besi yang mengakibatkan anemia 7 . Berdasarkan penelitian Algafari, B. M dan Muh.…”
Section: Pendahuluanunclassified
“…14 The clinical trials showed that giving moringa leaf extract at a dose of 2×1 with a content of 1,000 mg in female adolescents increased Hb levels after two months of intervention. 15 Another study also showed that giving 2×2 doses of moringa leaf flour capsules containing 500 mg of flour per capsule in the morning and evening for 12 weeks was able to increase the Hb levels of female adolescents. 13 Changes in Hb levels in the control group of 14 people (58.3%) with an increase in Hb levels of 0.3-3.5 g/dL who were not given moringa leaf flour, while in the intervention group, the changes in Hb levels were 22 people (91.7%) with an increase in Hb levels of 1.5-2.2 g/dL after being given moringa leaf flour.…”
Section: Introductionmentioning
confidence: 97%